Intra-rater reliability, measurement precision, and inter-test correlations of 1RM single-leg leg-press, knee-flexion, and knee-extension in uninjured adult agility-sport athletes: Considerations for right and left unilateral measurements in knee injury control. (November 2019) - Clark, Nicholas C.; Reilly, Lee J.; Davies, Stephanie C.
Abstract: Objectives: Knowledge of single-leg knee strength test reliability for the right and left limb is critical for between-limb clinical decision-making. Knowledge of between-test correlations is essential for understanding whether tests measure similar or different aspects of muscle strength. This study investigated the intra-rater, test-retest reliability and measurement precision of one repetition maximum (1RM) single-leg leg-press (LP), knee-flexion (KF), and knee-extension (KE) for both limbs, and inter-test correlations. Design: Repeated measures; Setting: University. Participants: Six males, seven females (age 25.6 ± 5.5 yr; height 171.4 ± 8.4 cm; mass 71.8 ± 13.4 kg). Main outcome measures: Normalised 1RM (percent body-mass (%BM)), intraclass correlation coefficient (ICC) (2, 1), standard error of measurement (SEM; %BM), Pearson's correlation ( r ), coefficient of determination ( r 2 ). Results: Mean 1RM test-retest values were (right, left): LP, 214.2–218.5%BM, 213.5–215.4%BM; KF, 35.9–38.9%BM, 37.7–38.2%BM; KE, 43.3–44.6%BM, 36.2–39.3%BM. The ICCs/SEMs were (right, left): LP, 0.98/7.3%BM, 0.94/14.2%BM; KF, 0.75/4.9%BM, 0.95/1.9%BM; KE, 0.87/3.4%BM, 0.78/4.4%BM. Correlations were significant ( P  < 0.01), r / r 2 values were: LP-KF, 0.60/0.36; LP-KE, 0.59/0.35; KF-KE, 0.50/0.25. Conclusions: Tests demonstrated good reliability and measurement precision, although ICCs and SEMs were different between limbs. Tests were correlated, but only one-third of the variance was shared between tests. Practitioners should be cognisant of between-limb differences in reliability and include all tests for knee clinical decision-making. Highlights: 1RM single-leg leg-press, knee-flexion, and knee-extension showed good reliability. Test reliability was different between right and left limbs for all tests. Test reliability for one limb should not be extrapolated to the opposite limb. Inter-test correlations were statistically significant but shared variance was low. All 1RM tests should be used for thorough knee muscle strength assessment.